Comments on the guidelines (2018) of the European Society of Cardiology (ESC) and the European Society of Hypertension (ESH) on the management of arterial hypertension [Kommentar zu den Leitlinien (2018) der Europäischen Gesellschaft für Kardiologie (ESC) und der Europäischen Gesellschaft für Hypertonie (ESH) für das Management der arteriellen Hypertonie] - Mahfoud, F.; Boehm, M.; Bongarth, C. M.; Bosch, R.; Schmieder, Roland; Schunkert, H.; Stellbrink, C.; Trenkwalder, P.; Vonend, O.; Weil, J.; Kreutz, R. (Internist, 2019)
Arterial hypertension represents one of the most frequent chronic diseases that can lead to complications, such as stroke, dementia, heart attack, heart failure and renal failure. By 2025 the number of hypertensive patients will increase to approximately 1.6 billion people worldwide. The new guidelines of the European Society of Cardiology (ESC) and the European Society of Hypertension (ESH) on the management of arterial hypertension replace the guidelines of the ESC/ESH from 2013. The 2018 guidelines of the ESC/ESH were adopted by the German Cardiac Society and the German Hypertension League. In these comments national characteristics are worked out and the essential new aspects of the guidelines are critically discussed. These include, for example, the definition of hypertension, the importance of out of office blood pressure measurements, revised blood pressure targets, the modified algorithm for drug treatment and the relevance of device-based hypertension treatments. Important aspects for the management of hypertensive emergencies are also presented.
CRIS-Team Scopus Importer:2019-05-07
Keywords: Device-based hypertension treatment; Fixed combination; Guidelines; Hypertension; Hypertensive emergencies; Target blood pressure